Composite silicon-carbon negative electrode material and preparation method and application thereof

By performing high-temperature closed-cell treatment on porous carbon materials and forming graphite microcrystalline layers, combined with nano-silicon particle deposition, the problem of insufficient rate performance and conductivity of silicon carbon negative electrode materials is solved, and the stability and performance of the battery are significantly improved.

CN119725471APending Publication Date: 2025-03-28NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD

Patent Information

Application Number
CN202411930869.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The current silicon-carbon negative electrode materials have poor rate performance and conductivity, and a volume expansion effect will occur during the charge and discharge cycle, resulting in poor rate and cycle stability of lithium batteries.

Method used

By performing high-temperature closed-pore treatment on the porous carbon material, a modified hole is formed, and a graphite microcrystalline layer is formed around the hole, and nanosilicon particles are moderately deposited to form a composite silicon carbon negative electrode material.

Benefits of technology

It significantly reduces the resistivity of the material, improves the electrical and rate performance of silicon carbon negative electrode materials, reduces the volume expansion rate, and improves the stability of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725471A_ABST
    Figure CN119725471A_ABST
Patent Text Reader

Abstract

The invention provides a composite silicon-carbon negative electrode material as well as a preparation method and application thereof. The composite silicon-carbon negative electrode material comprises a composite silicon-carbon inner core and a carbon coating layer arranged on the surface of the composite silicon-carbon inner core, the composite silicon-carbon inner core comprises a porous carbon skeleton and nano silicon particles, modified holes are formed in the porous carbon skeleton, graphite microcrystalline layers are arranged around openings of the modified holes, and the nano silicon particles are arranged on the surface of the porous carbon skeleton and in the modified holes. The modified holes are formed in the composite silicon-carbon negative electrode material, silicon particles can be properly deposited in the modified holes, and the graphite microcrystalline layer is arranged around the modified holes, so that the resistivity of the material can be greatly reduced, and the electrical property of the silicon-carbon negative electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to a composite silicon-carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] With the development of science and technology, the preparation technology of new materials, porous materials and silicon-carbon materials has received extensive attention and development. Silicon-carbon negative electrode material is a new type of negative electrode material, mainly used in lithium-ion batteries and energy storage systems. It is composed of two elements, silicon and carbon, combining the high capacity characteristics of silicon and the good conductivity and stability of carbon. Porous carbon materials are widely used in silicon-carbon negative electrode materials because of their advantages such as high specific surface area, good adsorption and chemical stability.

[0003] However, some silicon-carbon anode materials currently prepared from porous carbon materials have poor rate performance and conductivity, and also experience volume expansion during the charge and discharge cycle, which ultimately leads to poor rate and cycle stability of lithium batteries. This limits the application of silicon-carbon anodes to a certain extent.

[0004] CN118026153A discloses a porous carbon material with nanopores arranged in a directional manner, and a preparation method and application thereof, which belongs to the technical field of porous carbon material preparation. The porous carbon material prepared by the present invention has a pore structure of a combination of micropores and mesopores, the pore length "entirely penetrates" the porous carbon particle body, and each micropore and mesopore is directional and arranged along the pore length direction. The steps of the method are cumbersome and costly.

[0005] CN117902576A discloses a spherical porous carbon used as a negative electrode material and a preparation method thereof, as well as a lithium ion battery. The preparation method comprises the following steps: selecting a carbon fine powder raw material A for carbonization, crushing after carbonization to obtain a carbon fine powder A, wherein the carbonization temperature is 300-1500°C; mixing the carbon fine powder A with a mother solution B in proportion, heating and polymerizing to obtain a spherical carbon precursor, wherein the mother solution B is an organic carbon precursor, and the heating and polymerization temperature is 80-450°C; separating the spherical carbon precursor from the mother solution B to obtain a spherical carbon precursor; carbonizing the spherical carbon precursor to obtain a spherical carbon; adding an activation pore-forming agent to activate and form pores in the spherical carbon to obtain a spherical porous carbon; washing and purifying the activated and formed pores in the spherical porous carbon to obtain a pure spherical porous carbon used as a negative electrode material. The method described cannot guarantee that macropores and micropores will not be generated together during the activation process, and large pores will exist inside. It has high requirements on raw materials and activation conditions, and fails to improve the conductive properties of silicon-carbon composite materials.

[0006] CN117466280A discloses a porous carbon material and a preparation method thereof, a silicon-carbon negative electrode material and its preparation and application. The material can reduce the risk of silane deposition at the defective structure of the porous carbon material to form too small silicon-containing particles, but the uniformity of silane deposition cannot be guaranteed and the overall electrochemical performance of the material is not significantly improved.

[0007] The production cost of the above solution is high, and some functional groups will be formed inside the material, making it difficult to control the distribution and morphology of silicon or bond with silicon materials, affecting its ability and efficiency of lithium insertion and extraction, resulting in unstable performance of silicon-carbon composite materials and significant volume expansion effect. In addition, the tap density and conductivity of the silicon-carbon composite material obtained by the above solution still need to be improved, which limits its performance in applications such as batteries. Summary of the invention

[0008] The purpose of the present invention is to provide a composite silicon-carbon negative electrode material and a preparation method and application thereof. The composite silicon-carbon negative electrode material of the present invention is provided with modified pores, and the modified pores can appropriately deposit silicon particles. A graphite microcrystalline layer is provided around the modified pores, which can greatly reduce the resistivity of the material and improve the electrical properties of the silicon-carbon negative electrode material.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a composite silicon-carbon negative electrode material, the composite silicon-carbon negative electrode material comprising a composite silicon-carbon core and a carbon coating layer disposed on the surface of the composite silicon-carbon core;

[0011] The composite silicon-carbon core comprises a porous carbon skeleton and nano-silicon particles. The porous carbon skeleton is provided with modified holes. A graphite microcrystalline layer is provided around the openings of the modified holes. The nano-silicon particles are provided on the surface of the porous carbon skeleton and inside the modified holes.

[0012] The present invention modifies the holes on the porous carbon skeleton and forms a graphite microcrystalline layer around the holes. The graphite microcrystalline layer can improve the conductivity of the material, significantly reduce the powder resistivity of the material, and improve the rate performance of the battery. During the modification process, the pore size of the original holes on the porous carbon skeleton can be appropriately reduced, and while the specific surface area of ​​the porous carbon material is appropriately reduced, the pore volume inside which silicon can be effectively deposited is retained, and excessive growth of silicon grains in large pores is avoided.

[0013] Preferably, the average pore size of the modified holes is 3 nm to 6 nm, for example, 3 nm, 3.5 nm, 4 nm, 5 nm or 6 nm, etc., and is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0014] Preferably, taking the number of modified pores of the porous carbon skeleton as 100%, the proportion of mesopores in the porous carbon skeleton is 40% to 60%, for example: 40%, 45%, 50%, 55% or 60%, etc., not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0015] The mesopores described in the present invention are holes with a pore size of 2nm to 50nm, and the mesopore ratio is the ratio of the number of holes with a pore size of 2nm to 50nm in the modified holes in the porous carbon skeleton.

[0016] Preferably, the intensity ratio of the D peak to the G peak of the porous carbon skeleton is ID / IG of 0.3 to 1.0, for example, 0.3, 0.5, 0.7, 0.9 or 1.0, etc., not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Preferably, the pore volume of the porous carbon skeleton is 0.3 cm 3 / g~1.5cm 3 / g, for example: 0.3cm 3 / g, 0.5cm 3 / g, 0.8cm 3 / g, 1cm 3 / g or 1.5cm 3 / g, etc., are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] Preferably, the specific surface area of ​​the porous carbon skeleton is 200 cm 2 / g~2500cm 2 / g, for example: 200cm 2 / g、500cm 2 / g、1000cm 2 / g、2000cm 2 / g or 2500cm 2 / g, etc., are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the interlayer spacing d of the graphite microcrystalline layer is 002 for For example: or The present invention is not limited to the numerical values ​​listed, and other numerical values ​​not listed within the numerical range are also applicable.

[0019] Preferably, the thickness of the carbon coating layer is 1 nm to 100 nm, for example, 1 nm, 5 nm, 10 nm, 20 nm or 100 nm, etc., and is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] Preferably, the resistance of the composite silicon-carbon negative electrode material is 0.5 to 1.6 Ω / cm, for example, 0.5 Ω / cm, 0.8 Ω / cm, 1 Ω / cm, 1.2 Ω / cm or 1.6 Ω / cm.

[0021] Preferably, the specific surface area of ​​the composite silicon-carbon negative electrode material is 1 m 2 / g~5m 2 / g, for example: 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g or 5m 2 / g, etc., are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the tap density of the composite silicon-carbon negative electrode material is 0.5 g / m 3 ~1.8g / m 3 , for example: 0.5g / m 3 , 0.8g / m 3 , 1g / m 3 , 1.5g / m 3 or 1.8g / m 3 The present invention is not limited to the numerical values ​​listed, and other numerical values ​​not listed within the numerical range are also applicable.

[0023] Preferably, the volume expansion rate of the composite silicon-carbon negative electrode material is 1% to 20%, for example: 1%, 5%, 10%, 15% or 20%, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In a second aspect, the present invention provides a method for preparing the composite silicon-carbon negative electrode material as described in the first aspect, the preparation method comprising the following steps:

[0025] (1) subjecting the porous carbon material to a high-temperature pore-closing treatment to obtain a porous carbon skeleton;

[0026] (2) performing a first chemical vapor deposition treatment on the porous carbon skeleton using a mixture of a protective gas and a gaseous silicon source to obtain a precursor material;

[0027] (3) Using a gaseous carbon source to perform a second chemical vapor deposition treatment on the precursor material to obtain the composite silicon-carbon negative electrode material.

[0028] The present invention performs high-temperature pore closing treatment on the porous carbon material, so that the large-diameter pores in the porous carbon material shrink and generate a graphite microcrystalline layer on the surface of the pores, which can not only improve the uniformity of the pore diameter and the uniformity of subsequent silicon particle deposition, but the generated graphite microcrystalline layer can also reduce the resistivity of the material and improve the material's electrical conductivity and rate performance.

[0029] Preferably, the porous carbon material in step (1) is obtained by subjecting a solid carbon source to a pore-forming activation treatment.

[0030] Preferably, the solid carbon source includes any one of biomass carbon materials, sugars, resins, petroleum coke, asphalt or anthracite, or a combination of at least two of them. Typical but non-limiting combinations include a combination of biomass carbon materials and sugars, a combination of petroleum coke and asphalt, or a combination of resin and petroleum coke, etc., preferably a biomass carbon material.

[0031] Preferably, the biomass carbon material comprises coconut shell charcoal.

[0032] Preferably, the pore-forming activation treatment includes any one of gas phase activation, solid phase pyrolysis or hydrothermal methods, or a combination of at least two of them. Typical but non-limiting combinations include a combination of gas phase activation and hydrothermal methods, a combination of solid phase pyrolysis and hydrothermal methods, or a combination of gas phase activation and solid phase pyrolysis, etc., preferably solid phase pyrolysis.

[0033] Preferably, the solid phase pyrolysis method comprises: mixing a solid carbon source with an activator and subjecting the mixture to heat treatment to obtain a porous carbon material.

[0034] Preferably, the activator comprises potassium hydroxide and / or sodium hydroxide.

[0035] Preferably, the mass ratio of the solid carbon source to the activator is 1:(0.5-3), for example: 1:0.5, 1:0.8, 1:1, 1:2 or 1:3, etc., not limited to the listed values, other unlisted values ​​within the numerical range are also applicable, preferably 1:(2-3).

[0036] Preferably, the atmosphere of the heat treatment includes an inert atmosphere.

[0037] Preferably, the heat treatment temperature is 750°C to 950°C, for example, 750°C, 800°C, 850°C, 900°C or 950°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the heat treatment time is 100 min to 300 min, for example, 100 min, 150 min, 200 min, 250 min or 300 min, etc., not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0039] Preferably, the heat treatment is followed by washing and drying.

[0040] Preferably, taking the number of pores in the porous carbon material as 100%, the proportion of mesopores in the porous carbon material is 5% to 15%, for example: 5%, 8%, 10%, 12% or 15%, etc., not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0041] Preferably, the temperature of the high-temperature closed-cell treatment in step (1) is 1000°C to 2000°C, for example: 1000°C, 1200°C, 1500°C, 1800°C or 2000°C, etc., not limited to the listed values, other unlisted values ​​within the numerical range are also applicable, preferably 1100°C to 2000°C.

[0042] Preferably, the time of the high-temperature pore closing treatment in step (1) is 30 min to 300 min, for example, 30 min, 50 min, 100 min, 200 min or 300 min, etc., and is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0043] Preferably, the intensity ratio of the D peak to the G peak at the opening of the pores in the porous carbon material is ID1 / IG1, and the intensity ratio of the D peak to the G peak at the opening of the modified pores in the porous carbon skeleton obtained after the high-temperature closed-pore treatment is ID2 / IG2, ID2 / IG2-ID1 / IG1=0.15~0.3, for example: 0.15, 0.18, 0.2, 0.25 or 0.3, etc.

[0044] Since the pores are small in diameter and numerous in number, the intensity ratio of the D peak to the G peak at the opening of the pores in the porous carbon material of the present invention and the intensity ratio of the D peak to the G peak at the opening of the modified pores in the porous carbon skeleton obtained after high-temperature pore closing treatment are both average values ​​obtained by measuring multiple holes in the same range of the same particles before and after treatment.

[0045] It can be seen from the obvious decrease in the strength ratio of the modified pores after high-temperature closure that the degree of graphitization at the pore openings increased, that is, a graphite microcrystalline layer was produced.

[0046] Preferably, the protective gas in step (2) includes nitrogen and / or argon.

[0047] Preferably, the gaseous silicon source in step (2) comprises silane and / or disilane.

[0048] Preferably, the volume ratio of the protective gas and the gaseous silicon source in step (2) is (1-10):1, for example: 1:1, 2:1, 5:1, 8:1 or 10:1, etc., and is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] Preferably, the flow rate of the mixed gas in step (2) is 5 L / h to 20 L / h, for example 5 L / h, 8 L / h, 10 L / h, 15 L / h or 20 L / h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] Preferably, the temperature of the first chemical vapor deposition treatment in step (2) is 400°C to 650°C, for example 400°C, 450°C, 500°C, 600°C or 650°C, etc., and is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] Preferably, the time of the first chemical vapor deposition treatment in step (2) is 1 h to 10 h, for example: 1 h, 2 h, 5 h, 8 h or 10 h, etc., not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0052] Preferably, the gaseous carbon source in step (3) includes any one of methane, ethane, acetylene, ethylene or propane, or a combination of at least two of them. Typical but non-limiting combinations include a combination of methane and ethane, a combination of ethane and acetylene, or a combination of ethylene and propane.

[0053] Preferably, the flow rate of the gaseous carbon source in step (3) is 1 L / h to 10 L / h, for example: 1 L / h, 2 L / h, 5 L / h, 8 L / h or 10 L / h, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] Preferably, the temperature of the second chemical vapor deposition treatment in step (3) is 650°C to 950°C, for example: 650°C, 700°C, 800°C, 900°C or 950°C, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] Preferably, the time for the second chemical vapor deposition treatment in step (3) is 1 h to 5 h, for example: 1 h, 2 h, 3 h, 4 h or 5 h, etc., not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0056] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the composite silicon-carbon negative electrode material as described in the first aspect.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] (1) The composite silicon-carbon negative electrode material of the present invention is provided with modified pores, and the modified pores can appropriately deposit silicon particles. A graphite microcrystalline layer is provided around the modified pores, which can greatly reduce the resistivity of the material and improve the electrical properties of the silicon-carbon negative electrode material.

[0059] (2) In the porous carbon skeleton of the composite silicon-carbon negative electrode material of the present invention, the total pore volume of the modified pores can reach 0.97 cm 3 / g, the mesopore volume can reach 0.91cm 3 / g, the ID / IG before high-temperature pore-closing treatment is above 0.94, and after high-temperature pore-closing treatment, the ID / IG can be reduced to about 0.18, and the specific surface area of ​​the porous carbon skeleton can reach 1986m 2 / g or less, and the average pore size of the modified pores is between 2.5nm and 5.5nm. The specific surface area of ​​the composite silicon-carbon negative electrode material can reach 2.67m 2 / g, the tap density can reach 1.01g / cm 3 The above powder resistance can reach within 1.56Ω / cm. After being made into a battery, the 0.1C first charge specific capacity of the battery can reach more than 1711mAh / g, the first cycle efficiency can reach more than 86.9%, the 1C charge specific capacity can reach more than 1622mAh / g, and the volume expansion rate can reach within 15.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is a schematic diagram of the structure of the composite silicon-carbon negative electrode material described in Example 1 of the present invention, wherein 1 is a porous carbon skeleton, 2 is a modified hole, 3 is a graphite microcrystalline layer, 4 is a nano-silicon particle, and 5 is a carbon coating layer.

[0061] Figure 2 This is a transmission electron microscope image of the composite silicon-carbon negative electrode material described in Example 1 of the present invention. DETAILED DESCRIPTION

[0062] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0063] Example 1

[0064] This embodiment provides a composite silicon-carbon negative electrode material, and the composite silicon-carbon negative electrode material is prepared by the following method:

[0065] (1) 300 g of potassium hydroxide and 100 g of coconut shell charcoal were fully mixed and placed in a tube furnace for heat treatment at 850 ° C in an argon atmosphere for 200 min. The collected black powder was etched in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water for 3 times, filtered and dried to obtain a porous carbon material with a mesopore ratio of 13.7%;

[0066] (2) subjecting the porous carbon material to a high-temperature pore-closing treatment at 1500° C. for 150 min to obtain a porous carbon skeleton with a mesopore ratio of 51.5%;

[0067] (3) placing the porous carbon skeleton in a new rotary furnace, introducing a mixed gas of silane and argon with a volume ratio of 1:5 at a rate of 10 L / h at 500°C, and depositing for 3 hours to obtain a precursor;

[0068] (4) Methane was introduced at a rate of 5 L / h to vapor-deposit the precursor at 750° C. for 2 h. After cooling to room temperature, the composite silicon-carbon negative electrode material was obtained.

[0069] The structural schematic diagram of the composite silicon-carbon negative electrode material is as follows Figure 1 As shown, the composite silicon-carbon negative electrode material includes a porous carbon skeleton 1, on which modified pores 2 are arranged, at the openings of the modified pores 2 a graphite microcrystalline layer 3 is arranged, on the surface and inside of the modified pores 2 nano-silicon particles 4 are arranged, and the porous carbon skeleton 1 is externally coated with a carbon coating layer 5.

[0070] The transmission electron microscope image of the composite silicon-carbon negative electrode material is as follows Figure 2 The interlayer spacing d of the graphite microcrystalline layer in the composite silicon-carbon negative electrode material is 002 for The median particle size D50 of the nano-silicon particles is 2.4 nm, and the thickness of the carbon coating layer is 50 nm.

[0071] Example 2

[0072] This embodiment provides a composite silicon-carbon negative electrode material, and the composite silicon-carbon negative electrode material is prepared by the following method:

[0073] (1) 300 g of potassium hydroxide and 100 g of anthracite were fully mixed and placed in a tube furnace for heat treatment at 850° C. in an argon atmosphere for 200 min. The collected black powder was etched in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water for 3 times, filtered and dried to obtain a porous carbon material with a mesopore ratio of 13.5%;

[0074] (2) subjecting the porous carbon material to a high-temperature pore-closing treatment at 1400° C. for 150 min to obtain a porous carbon skeleton with a mesopore ratio of 46.3%;

[0075] (3) placing the porous carbon skeleton in a new rotary furnace, introducing a mixed gas of silane and argon with a volume ratio of 1:5 at a rate of 10 L / h at 500°C, and depositing for 3 hours to obtain a precursor;

[0076] (4) Methane was introduced at a rate of 5 L / h to vapor-deposit the precursor at 750° C. for 2 h. After cooling to room temperature, the composite silicon-carbon negative electrode material was obtained.

[0077] The interlayer spacing d of the graphite microcrystalline layer in the composite silicon-carbon negative electrode material 002 for The median particle size D50 of the nano-silicon particles is 2.9 nm, and the thickness of the carbon coating layer is 60 nm.

[0078] Example 3

[0079] This embodiment provides a composite silicon-carbon negative electrode material, and the composite silicon-carbon negative electrode material is prepared by the following method:

[0080] (1) 300 g of potassium hydroxide and 100 g of petroleum coke were fully mixed and placed in a tube furnace for heat treatment at 850° C. in an argon atmosphere for 200 min. The collected black powder was etched in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water for 3 times, filtered and dried to obtain a porous carbon material with a mesopore ratio of 10.9%;

[0081] (2) subjecting the porous carbon material to a high-temperature pore-closing treatment at 1300° C. for 150 min to obtain a porous carbon skeleton with a mesopore ratio of 43.8%;

[0082] (3) placing the porous carbon skeleton in a new rotary furnace, introducing a mixed gas of silane and argon with a volume ratio of 1:5 at a rate of 10 L / h at 500°C, and depositing for 3 hours to obtain a precursor;

[0083] (4) Methane was introduced at a rate of 5 L / h to vapor-deposit the precursor at 750° C. for 2 h. After cooling to room temperature, the composite silicon-carbon negative electrode material was obtained.

[0084] The interlayer spacing d of the graphite microcrystalline layer in the composite silicon-carbon negative electrode material 002 for The median particle size D50 of the nano-silicon particles is 3.5 nm, and the thickness of the carbon coating layer is 60 nm.

[0085] Example 4

[0086] This embodiment provides a composite silicon-carbon negative electrode material, and the composite silicon-carbon negative electrode material is prepared by the following method:

[0087] (1) 300 g of potassium hydroxide and 100 g of coconut shell charcoal were fully mixed and placed in a tube furnace for heat treatment at 850 ° C in an argon atmosphere for 200 min. The collected black powder was etched in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water for 3 times, filtered and dried to obtain a porous carbon material with a mesopore ratio of 12.6%;

[0088] (2) subjecting the porous carbon material to a high-temperature pore-closing treatment at 1200° C. for 150 min to obtain a porous carbon skeleton with a mesopore ratio of 43.5%;

[0089] (3) placing the porous carbon skeleton in a new rotary furnace, introducing a mixed gas of silane and argon with a volume ratio of 1:5 at a rate of 10 L / h at 500°C, and depositing for 3 hours to obtain a precursor;

[0090] (4) Methane was introduced at a rate of 5 L / h to vapor-deposit the precursor at 750° C. for 2 h. After cooling to room temperature, the composite silicon-carbon negative electrode material was obtained.

[0091] Example 5

[0092] This embodiment provides a composite silicon-carbon negative electrode material, and the composite silicon-carbon negative electrode material is prepared by the following method:

[0093] (1) 300 g of potassium hydroxide and 100 g of coconut shell charcoal were fully mixed and placed in a tube furnace for heat treatment at 850 ° C in an argon atmosphere for 200 min. The collected black powder was etched in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water for 3 times, filtered and dried to obtain a porous carbon material with a mesopore ratio of 13.2%;

[0094] (2) subjecting the porous carbon material to a high-temperature pore-closing treatment at 1100° C. for 150 min to obtain a porous carbon skeleton with a mesopore ratio of 41.6%;

[0095] (3) placing the porous carbon skeleton in a new rotary furnace, introducing a mixed gas of silane and argon with a volume ratio of 1:5 at a rate of 10 L / h at 500°C, and depositing for 3 hours to obtain a precursor;

[0096] (4) Methane was introduced at a rate of 5 L / h to vapor-deposit the precursor at 750° C. for 2 h. After cooling to room temperature, the composite silicon-carbon negative electrode material was obtained.

[0097] Example 6

[0098] This embodiment provides a composite silicon-carbon negative electrode material, and the composite silicon-carbon negative electrode material is prepared by the following method:

[0099] (1) 200 g of potassium hydroxide and 100 g of coconut shell charcoal were fully mixed and placed in a tube furnace for heat treatment at 850 ° C in an argon atmosphere for 200 min. The collected black powder was etched in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water for 3 times, filtered and dried to obtain a porous carbon material with a mesopore ratio of 9.4%;

[0100] (2) subjecting the porous carbon material to a high-temperature pore-closing treatment at 1100° C. for 150 min to obtain a porous carbon skeleton with a mesopore ratio of 40.3%;

[0101] (3) placing the porous carbon skeleton in a new rotary furnace, introducing a mixed gas of silane and argon with a volume ratio of 1:5 at a rate of 10 L / h at 500°C, and depositing for 3 hours to obtain a precursor;

[0102] (4) Methane was introduced at a rate of 5 L / h to vapor-deposit the precursor at 750° C. for 2 h. After cooling to room temperature, the composite silicon-carbon negative electrode material was obtained.

[0103] Example 7

[0104] This embodiment provides a composite silicon-carbon negative electrode material, and the composite silicon-carbon negative electrode material is prepared by the following method:

[0105] (1) 300 g of potassium hydroxide and 100 g of coconut shell charcoal were fully mixed and placed in a tube furnace for heat treatment at 850 ° C in an argon atmosphere for 200 min. The collected black powder was etched in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water for 3 times, filtered and dried to obtain a porous carbon material with a mesopore ratio of 12.9%;

[0106] (2) subjecting the porous carbon material to a high-temperature pore-closing treatment at 1800° C. for 150 min to obtain a porous carbon skeleton with a mesopore ratio of 53.8%;

[0107] (3) placing the porous carbon skeleton in a new rotary furnace, introducing a mixed gas of silane and argon with a volume ratio of 1:5 at a rate of 10 L / h at 500°C, and depositing for 3 hours to obtain a precursor;

[0108] (4) Methane was introduced at a rate of 5 L / h to vapor-deposit the precursor at 750° C. for 2 h. After cooling to room temperature, the composite silicon-carbon negative electrode material was obtained.

[0109] Example 8

[0110] This embodiment provides a composite silicon-carbon negative electrode material, and the composite silicon-carbon negative electrode material is prepared by the following method:

[0111] (1) 300 g of potassium hydroxide and 100 g of coconut shell charcoal were fully mixed and placed in a tube furnace for heat treatment at 850 ° C in an argon atmosphere for 200 min. The collected black powder was etched in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water for 3 times, filtered and dried to obtain a porous carbon material with a mesopore ratio of 13.2%;

[0112] (2) subjecting the porous carbon material to a high-temperature pore-closing treatment at 1900° C. for 150 min to obtain a porous carbon skeleton with a mesopore ratio of 55.1%;

[0113] (3) placing the porous carbon skeleton in a new rotary furnace, introducing a mixed gas of silane and argon with a volume ratio of 1:5 at a rate of 10 L / h at 500°C, and depositing for 3 hours to obtain a precursor;

[0114] (4) Methane was introduced at a rate of 5 L / h to vapor-deposit the precursor at 750° C. for 2 h. After cooling to room temperature, the composite silicon-carbon negative electrode material was obtained.

[0115] Example 9

[0116] This embodiment provides a composite silicon-carbon negative electrode material, and the composite silicon-carbon negative electrode material is prepared by the following method:

[0117] (1) 300 g of potassium hydroxide and 100 g of coconut shell charcoal were fully mixed and placed in a tube furnace for heat treatment at 850 ° C in an argon atmosphere for 200 min. The collected black powder was etched in 1 mol / L hydrochloric acid for 6 h, then rinsed with ethanol and deionized water for 3 times, filtered and dried to obtain a porous carbon material with a mesopore ratio of 13.4%;

[0118] (2) subjecting the porous carbon material to a high-temperature pore-closing treatment at 2000° C. for 150 min to obtain a porous carbon skeleton with a mesopore ratio of 58.6%;

[0119] (3) placing the porous carbon skeleton in a new rotary furnace, introducing a mixed gas of silane and argon with a volume ratio of 1:5 at a rate of 10 L / h at 500°C, and depositing for 3 hours to obtain a precursor;

[0120] (4) Methane was introduced at a rate of 5 L / h to vapor-deposit the precursor at 750° C. for 2 h. After cooling to room temperature, the composite silicon-carbon negative electrode material was obtained.

[0121] Example 10

[0122] The only difference between this embodiment and embodiment 1 is that step (1) is not performed, and commercial porous carbon material is directly used to perform high-temperature pore closing treatment at 1800° C. Other conditions and parameters are exactly the same as those in embodiment 1.

[0123] Embodiment 11

[0124] The only difference between this embodiment and embodiment 1 is that the mass of potassium hydroxide is 100 g, and other conditions and parameters are exactly the same as those in embodiment 1.

[0125] Example 12

[0126] The only difference between this embodiment and embodiment 1 is that the temperature of the high-temperature pore closing treatment is 1000° C., and the other conditions and parameters are exactly the same as those in embodiment 1.

[0127] Example 13

[0128] The only difference between this embodiment and embodiment 1 is that the temperature of the high-temperature pore closing treatment is 2200° C., and the other conditions and parameters are exactly the same as those in embodiment 1.

[0129] Comparative Example 1

[0130] The only difference between this comparative example and Example 1 is that high-temperature pore closing treatment is not performed, and other conditions and parameters are exactly the same as those in Example 1. The mesopore ratio of the porous carbon material is 13.7%.

[0131] Comparative Example 2

[0132] In this comparative example, the commercially purchased porous carbon material was placed in a new rotary kiln, heat treated at 500°C in a silane and argon atmosphere for 3 hours, then methane gas was introduced for 2 hours, and after cooling to room temperature, the final silicon-based negative electrode material was obtained.

[0133] Comparative Example 3

[0134] The only difference between this comparative example and Example 1 is that step (4) of depositing the carbon coating layer is not performed, and the other conditions and parameters are exactly the same as those in Example 1.

[0135] Performance Test:

[0136] The properties of the porous carbon skeletons obtained in the examples and comparative examples were tested respectively (Comparative Example 1 directly tested the porous carbon material, i.e., the porous carbon material without closed-cell treatment), and the test results are shown in Table 1:

[0137] Table 1

[0138]

[0139]

[0140] The composite silicon-carbon negative electrode material prepared in the embodiment and the comparative example was tested for its properties, wherein the specific surface area of ​​the material was measured by a JW-BK300C high-performance specific surface area and pore size analyzer, the tap density was measured by a JZ-tap density measuring instrument, and the powder resistance was measured by a FTDZ-I powder material resistivity tester. 70wt.% of the composite silicon-carbon negative electrode material, 15wt.% of acetylene black and 15wt.% of PVDF were mixed evenly to form a slurry, which was evenly coated on a copper foil, and then vacuum dried and stamped into a circular electrode sheet, with metallic lithium as the counter electrode, 1mol / L LiPF6 / DMC+DEC+EC (volume ratio of 1:1:1) as the electrolyte, and Celgard2400 as the diaphragm to form a test battery. The battery was tested, and the test results are shown in Table 2:

[0141] Table 2

[0142]

[0143]

[0144] As can be seen from Table 1-2, from Examples 1-13, the total pore volume of the modified pores in the porous carbon skeleton of the composite silicon-carbon negative electrode material of the present invention can reach 0.97 cm 3 / g, the mesopore volume can reach 0.91cm 3 / g, the ID / IG before high-temperature pore-closing treatment is above 0.94, and after high-temperature pore-closing treatment, the ID / IG can be reduced to about 0.18, and the specific surface area of ​​the porous carbon skeleton can reach 1986m 2 / g or less, and the average pore size of the modified pores is between 2.5nm and 5.5nm. The specific surface area of ​​the composite silicon-carbon negative electrode material can reach 2.67m 2 / g, the tap density can reach 1.01g / cm 3 The above powder resistance can reach within 1.56Ω / cm. After it is made into a battery, the 0.1C first charge specific capacity of the battery can reach more than 1711mAh / g, the first cycle efficiency can reach more than 86.9%, the 1C charge specific capacity can reach more than 1622mAh / g, and the volume expansion rate is controlled within 15.5%. The reason is that the high-temperature closed pores greatly increase the proportion of mesopores on the porous carbon skeleton, which can more fully adsorb the silicon source gas, so that silicon can be deposited inside the pores, and the silicon particles deposited in the mesopores have more sufficient expansion space to avoid the outward expansion of the material during the charge and discharge process. The graphite microcrystalline layer can not only improve the electrical conductivity of the material, but also stabilize the mesopores. The rigidity of the porous carbon skeleton is significantly improved, the structure is stable, and a stable shape can be maintained during the charge and discharge process, and the volume expansion rate is also reduced accordingly.

[0145] By comparing Example 1 with Example 10, it can be seen that the method for preparing the composite silicon-carbon negative electrode material of the present invention can select porous carbon materials obtained by various means, and can achieve good results.

[0146] By comparing Example 1 and Example 11, it can be seen that in the preparation process of the composite silicon-carbon negative electrode material of the present invention, the amount of activator added will affect the pore-forming effect, and thus affect the performance of the material. When the mass ratio of the activator to the carbon material is controlled at 2 to 3:1, the activation effect is better. If the amount of activator added is insufficient, the porosity of the material will drop significantly and the pore-forming effect will deteriorate.

[0147] By comparing Example 1 with Examples 12-13, it can be seen that during the preparation process of the composite silicon-carbon negative electrode material of the present invention, the temperature of the high-temperature closed-pore treatment will affect its performance. When the temperature of the high-temperature closed-pore treatment is controlled at 1100°C to 2000°C, the closed-pore effect is better and the material performance is excellent. If the temperature of the high-temperature closed-pore treatment is too low, the macropores have no good modification effect, and it is difficult to form a graphite microcrystalline layer of a suitable size, resulting in a high volume expansion of the composite silicon-carbon negative electrode material. If the temperature of the high-temperature closed-pore treatment is too high, too many graphite microcrystalline layers are formed, resulting in the negative electrode material The pore volume is too small, the subsequent deposited silicon content is low, and the battery capacity is low.

[0148] From the comparison between Example 1 and Comparative Example 1, it can be seen that the present invention performs a high-temperature pore closing treatment on the porous carbon material so that the large-diameter pores in the porous carbon material shrink and a graphite microcrystalline layer is generated on the surface of the pores. This can not only improve the uniformity of the pore diameter and the uniformity of subsequent silicon particle deposition, but the generated graphite microcrystalline layer can also reduce the resistivity of the material and improve the conductivity and rate performance of the material.

[0149] From the comparison between Example 10 and Comparative Example 2, it can be seen that after the commercial porous carbon material is subjected to high-temperature pore closing treatment, the performance of the material can be significantly improved.

[0150] From the comparison between Example 1 and Comparative Example 3, it can be seen that without the outer carbon layer, some of the deposited silicon particles may be exposed on the surface of the porous carbon matrix, resulting in a higher specific surface area of ​​the silicon-carbon material and the volume expansion cannot be well suppressed.

[0151] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite silicon-carbon negative electrode material, characterized in that: The composite silicon-carbon negative electrode material comprises a composite silicon-carbon core and a carbon coating layer arranged on the surface of the composite silicon-carbon core; The composite silicon-carbon core comprises a porous carbon skeleton and nano-silicon particles. The porous carbon skeleton is provided with modified holes. A graphite microcrystalline layer is provided around the openings of the modified holes. The nano-silicon particles are provided on the surface of the porous carbon skeleton and inside the modified holes.

2. The composite silicon-carbon negative electrode material according to claim 1, characterized in that: The average pore size of the modified pores is 3nm to 6nm; Preferably, taking the number of modified pores of the porous carbon skeleton as 100%, the proportion of mesopores in the porous carbon skeleton is 40% to 60%; Preferably, the intensity ratio ID / IG of the D peak to the G peak of the porous carbon skeleton is 0.3 to 1.0; Preferably, the pore volume of the porous carbon skeleton is 0.3 cm 3 / g~1.5cm 3 / g; Preferably, the specific surface area of ​​the porous carbon skeleton is 200 cm 2 / g~2500cm 2 / g.

3. The composite silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: The interlayer spacing d of the graphite microcrystalline layers 002 for Preferably, the median particle size D50 of the nano-silicon particles is 1.5 nm to 4 nm; Preferably, the carbon coating layer has a thickness of 1 nm to 100 nm.

4. The composite silicon-carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The resistance of the composite silicon-carbon negative electrode material is 0.5 to 1.6 Ω / cm; Preferably, the specific surface area of ​​the composite silicon-carbon negative electrode material is 1 m 2 / g~5m 2 / g; Preferably, the tap density of the composite silicon-carbon negative electrode material is 0.5 g / m 3 ~1.8g / m 3 ; Preferably, the volume expansion rate of the composite silicon-carbon negative electrode material is 1% to 20%.

5. A method for preparing the composite silicon-carbon negative electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) performing a high-temperature pore-closing treatment on the porous carbon material to obtain a porous carbon skeleton; (2) performing a first chemical vapor deposition treatment on the porous carbon skeleton using a mixture of a protective gas and a gaseous silicon source to obtain a precursor material; (3) Using a gaseous carbon source to perform a second chemical vapor deposition treatment on the precursor material to obtain the composite silicon-carbon negative electrode material.

6. The preparation method according to claim 5, characterized in that: The porous carbon material in step (1) is obtained by subjecting a solid carbon source to a pore-forming activation treatment; Preferably, the solid carbon source comprises any one or a combination of at least two of biomass carbon materials, sugars, resins, petroleum coke, asphalt or anthracite, preferably biomass carbon materials; Preferably, the biomass carbon material comprises coconut shell charcoal; Preferably, the pore-forming activation treatment comprises any one of gas phase activation method, solid phase pyrolysis method or hydrothermal method or a combination of at least two thereof, preferably solid phase pyrolysis method; Preferably, the solid phase pyrolysis method comprises: mixing a solid carbon source with an activator and subjecting the mixture to heat treatment to obtain a porous carbon material; Preferably, the activator comprises potassium hydroxide and / or sodium hydroxide; Preferably, the mass ratio of the solid carbon source to the activator is 1:(0.5-3), preferably 1:(2-3); Preferably, the atmosphere of the heat treatment comprises an inert atmosphere; Preferably, the temperature of the heat treatment is 750°C to 950°C; Preferably, the heat treatment time is 100 min to 300 min; Preferably, the heat treatment is followed by acid etching, washing and drying; Preferably, taking the number of pores in the porous carbon material as 100%, the proportion of mesopores in the porous carbon material is 5% to 20%.

7. The preparation method according to claim 5 or 6, characterized in that: The temperature of the high-temperature closed-cell treatment in step (1) is 1000° C. to 2000° C., preferably 1100° C. to 2000° C.; Preferably, the high temperature pore closing treatment time in step (1) is 30 min to 300 min; Preferably, the intensity ratio of the D peak to the G peak at the opening of the pores in the porous carbon material is ID1 / IG1, and the intensity ratio of the D peak to the G peak at the opening of the modified pores in the porous carbon skeleton obtained after the high-temperature pore closing treatment is ID2 / IG2, ID2 / IG2-ID1 / IG1=0.15~0.

3.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The protective gas in step (2) comprises nitrogen and / or argon; Preferably, the gaseous silicon source in step (2) comprises silane and / or disilane; Preferably, the volume ratio of the protective gas to the gaseous silicon source in step (2) is (1-10):1; Preferably, the flow rate of the mixed gas in step (2) is 5L / h to 20L / h; Preferably, the temperature of the first chemical vapor deposition treatment in step (2) is 400° C. to 650° C.; Preferably, the time of the first chemical vapor deposition treatment in step (2) is 1 h to 10 h.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The gaseous carbon source in step (3) includes any one of methane, ethane, acetylene, ethylene or propane, or a combination of at least two thereof; Preferably, the flow rate of the gaseous carbon source in step (3) is 1 L / h to 10 L / h; Preferably, the temperature of the second chemical vapor deposition treatment in step (3) is 650° C. to 950° C.; Preferably, the time for the second chemical vapor deposition treatment in step (3) is 1 hour to 5 hours.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite silicon-carbon negative electrode material as claimed in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Porous carbon material, preparation method of porous carbon material, silicon-carbon negative electrode material and preparation and application of silicon-carbon negative electrode material

    CN117466280A

  • Spherical porous carbon used as negative electrode material, preparation method thereof and lithium ion battery

    CN117902576A

Cited By

  • Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and battery

    CN120749157A

  • Silicon-carbon composite negative electrode material and preparation method and application thereof

    CN120933326A

  • Negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery

    CN121172083A

  • Coke-based porous carbon and preparation method thereof, silicon-carbon negative electrode material, negative electrode and battery

    CN121626989A